Modulating contact properties by molecular layers in organic thin‐film transistors - Li Sun; Yating Li; Jiacheng Xie; Liqi Zhou; Peng Wang; Jian‐Bin Xu; Yi Shi; Xinran Wang; Daowei He (Electron)
Abstract Advanced organic devices and circuits demand both ultrahigh charge carrier mobilities and ultralow‐resistance contacts. However, due to a larger access resistance in staggered organic thin‐film transistors (OTFTs), the achievement of ultralow contact resistance (Rc) is still a challenge. The modulation of contact resistance by molecular layers near the interface has been rarely reported. Here, we demonstrate that few‐layer organic single crystals are grown on hafnium oxide (HfO2) by solution‐shearing epitaxy. We utilize these organic crystals to fabricate bottom‐gate staggered OTFTs with different contact processes. The results show that the contact properties of OTFTs are obviously modulated by crystal layers. The tri‐layer (3L) evaporated‐Au C10‐DNTT OTFTs exhibit optimal electrical performance, including ultralow Rc of 5.6 Ω ∙ cm, recorded transfer length of 0.4 μm, field‐effect mobility over 14 cm2V−1s−1, threshold voltage lower than 0.3 V, and long‐term air stability over 8 months. The main cause is that the metal atoms can penetrate into the charge transport layer, with damage‐free, in 3L evaporated‐Au OTFTs; nevertheless, it cannot be realized in other cases. Due to layer stacking of conjugated molecules and polymers, our strategy can efficiently modulate the contact resistance to aid the development of high‐performance organic devices and circuits.